Penyelenggaraan Inovasi Daerah: Kelembagaan dan Mekanisme Penilaian Pasca Transformasi BSKDN - Rachman Kosasih; Tomy Veryanto Bawulang; Mohammad Rizky Luthfiah Aziz (Research and Development Agency Ministry of Home Affairs, 2025)
The implementation of regional innovation serves as a strategic instrument to promote local governance reform and enhance the quality of public service delivery. In Indonesia, the Regional Innovation Assessment (Penilaian Inovasi Daerah/PID) was developed as an evaluation and supervisory mechanism for public sector innovation under the Ministry of Home Affairs. However, institutional restructuring following the establishment of the National Research and Innovation Agency (BRIN) and the transformation of the Research and Development Agency (BPP) into the Agency for Domestic Policy Strategy (BSKDN) has generated institutional uncertainty and regulatory disharmony in the implementation of PID. This study aims to analyze institutional dynamics and their implications for the implementation of the Regional Innovation Assessment from a public sector innovation perspective. The research employs a qualitative approach based on a document-based policy study, utilizing regulatory and institutional analysis. Data were collected from statutory regulations, official government planning documents, regional innovation statistics from 2018–2023, and relevant academic literature on public innovation and institutional reform. The findings indicate that PID continues to operate as an administrative practice despite lacking explicit institutional legitimacy following organizational restructuring. The misalignment between innovation regulations, BSKDN’s mandate, and BRIN’s functions has led to fragmented governance of public innovation and may weaken the effectiveness of regional innovation development. The study underscores the need for regulatory harmonization and a collaborative governance model that clarifies institutional roles in policy formulation, research coordination, and innovation implementation to strengthen an adaptive and public value-oriented regional innovation ecosystem.